STUDY OF GENTIC PARAMETERS USING HALF DIALLEL CROSS IN MAIZE (Zea mays L.) - Mohammed S. Altaweel; Qusay A. Yousif (Mesopotamia Journal of Agriculture)
Five inbred lines of maize (Zea mays L.) were used in this study with ten hybrids which planted through spring and autumn seasons (2018) at the research station of the Field Crops Department/College of Agriculture and Forestry/University of Mosul, using Randomized Complete Block Design with three replications. The characters studied were date to tasseling, date to silking, plant height, number of leaves per plant, leaf area cm2, leave area index, number of ears per plant, ear length, number of rows per ear, number grains per row, 300 grain weight, grain yield per plant and oil percent %.The results showed that phenotypic, genetic and environmental variances were significant for all the characters for both seasons. The average degree of dominance was greater than one for number of leaves per plant, leaf area index, number of ears per plant, ear length, number of rows per ear, the number grains per row and oil percent. The broad sense heritability was high for plant height, leaf area, leaf area index, number of rows per ear, 300 grain weight, grain yield per plant, and oil percent for both seasons, while it was medium for number of leaves per plant, number of ears per plant, ear length, number grain per row, and low for date to tasseling, date to silking, at autumn season. The expected genetic advance values for all characters and for both seasons was high.